Novel biomarkers for the assessment of disease activity in patients with sarcoidosis: a case-control study - Hosny Masoud, Hosam; Moustafa Ali , Amani; AbdelWahab , Fatma; Abdel-Hamid, Hoda M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: The prognosis of sarcoidosis is challenging and largely depends on the persistence of disease activity and the degree of organ dysfunction. Various biomarkers have been evaluated for diagnosis, disease activity assessment, and prognosis. This study aimed to determine if the ratios of monocytes to high-density lipoprotein cholesterol (MHR), platelets to lymphocytes (PLR), neutrophils to lymphocytes (NLR), and lymphocytes to monocytes ratio (LMR) could be used as novel sarcoidosis activity markers. Methods: In a case-control study, 54 patients with biopsy-confirmed sarcoidosis were divided into two groups; group 1: consisted of 27 patients with active sarcoidosis who were newly diagnosed and treatment-naive, and group 2: consisted of 27 patients with inactive sarcoidosis who had been on treatment for at least 6 months. All patients were subjected to a comprehensive history, physical examination, laboratory tests, chest imaging, spirometry, and screening for extrapulmonary organ involvement by means of electrocardiogram and eye examination. Results: The mean age of the patients was 44 ± 11 years (79.6% were females & 20.4% were males). MHR, NLR, and LMR were significantly higher in patients with active sarcoidosis than in an inactive disease with a cut-off value of 8.6, a sensitivity of 81.5%, and a specificity of 70.4% (P-value < 0.001), a cut-off value of 1.95, sensitivity of 74% and specificity of 66.7% (P-value 0.007) and a cut-off value of < 4, a sensitivity of 81.5%, and a specificity of 85.2% (P-value < 0.001), respectively. In contrast, PLR was not statistically significant between active and inactive sarcoidosis patients. Conclusions: The lymphocytes monocytes ratio is a highly sensitive and specific biomarker that could be used to assess the disease activity in sarcoidosis patients.